Crime and Crime Control In Traditional Igbo Society Of Nigeria - Igbo, Emmanuel U.M. (2013)
The paper examines the concept of crime and crime control in traditional Igbo society. Crime in traditional Igbo society consisted of serious violations of standardized ways of behaviour, custom and tradition of the people. Crime was said to be an ‘abomination’, which had far-reaching social consequences not only for the offender but also his immediate family and close relatives. These consequences include ill-luck, disease and death. As a result, people tried to conform to the norms, customs, and tradition of their society to avoid being sanctioned by their communities or being infected with terrible and incurable diseases by the gods. The impression that one gets is that crime control in traditional Igbo society appears to have been more effective than crime control in present-day society. Keywords: Igbo traditional society, crime, social control theory, crime contro